Pengaruh Disiplin Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan Rumah Sakit Muhammadiyah Palembang - Haura, Putri Atikah; Choiriyah, choiriyah; Cahyani, Eni (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
The formulation of the problem in this study is as follows: 1) Is there an influence of work discipline and job satisfaction on the performance of employees of the Muhammadiyah Hospital Palembang? 2) Is there an influence of work discipline on the performance of employees of the Muhammadiyah Hospital Palembang? 3) Is job satisfaction influenced by the performance of employees of the Muhammadiyah Hospital Palembang? These questions serve as the guiding principles of our study, driving our research and analysis. The type of research used in this study is associative. The population in this study amounted to 221 employees, and the sample used in this study was 69 employees using a sampling technique called stratified random sampling. The analysis method used is qualitative, which is quantified. The data analysis technique used in this study is multiple linear regression analysis, F Test, t-test, and Determination Coefficient; the results of the F Hypothesis Test indicate that there is an influence of work discipline and job satisfaction on the performance of employees of Muhammadiyah Hospital Palembang. The results of the t-hypothesis test indicate that work discipline influences the performance of employees of the Muhammadiyah Hospital Palembang, and job satisfaction influences the performance of employees of the Muhammadiyah Hospital Palembang.